Tremor in Vascular Cognitive Impairment Raises the Possibility of Mixed Pathology With Lewy Body Disease - Chiu, Pai-Yi; Tzeng, Ray-Chang; Wei, Cheng-Yu; Hung, Guang-Uei; Hu, Chaur-Jong (Frontiers in Neuroscience, 2020)
Objectives Tremor is common in patients with Lewy body disease (LBD) and not rare in normal individuals. Prevalence of tremor in patients with vascular cognitive impairment (VCI) and its association with other comorbidities are seldom studied. The aim of this study was to investigate the patient characteristics of VCI associated with tremor and to evaluate the possibility of mixed pathology with LBD in these patients. Methods Retrospective analysis of a large population with VCI registered in the database of a regional healthcare system was performed. VCI patients were divided into tremor and non-tremor groups. The associated characteristics including demographics, clinical features in motor and non-motor domains, vascular risk factors, and neuroimaging features were compared between the tremor group and the non-tremor group. Results Among 1337 patients with VCI, 292 (21.8%) had tremor, while 1045 (78.2%) did not have tremor. The tremor group had significantly higher prevalence of all motor and non-motor LBD clinical features than the non-tremor group. The tremor group also demonstrated more severe neuropsychiatric symptoms. Among patients with tremor, patients having tremor onset earlier than stroke onset showed significantly higher prevalence of rapid eye movement sleep behavior disorder. All comparisons were adjusted for age and severity of dementia. Conclusion Tremor is a common comorbidity of VCI. VCI patients with tremor had a higher prevalence of motor and non-motor LBD features. These findings raised the possibility of VCI patients with tremor having high possibility of mixed pathology with LBD.